THE EFFECT OF CORPORATE GOVERNANCE AND FIRM’S CHARACTERISTICS ON THE QUALITY OF SUSTAINABILITY REPORTING ON COMPANIES IN INDONESIA - Triwacananingrum, Wijaya; Hamdari, Janice; Priscilla, Savira Sandra; Valerie, Valerie (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This study aims to provide empirical evidence regarding the effect of corporate governance and company characteristics on the quality of sustainability reporting. Where the corporate governance component used is the board size (BD_SZ), board independence (BD_ID) , and audit committee (AU_CM) while the characteristic component is the return on assets (ROA), current ratio (CR), leverage (DER) and company size (SIZE). The sampling method using purposive sampling method and for data analysis using multiple regression analysis methods with the help of the SPSS program application. This study uses a sample of 106 companies in Indonesia. Hypothesis testing results show that BD_SZ and ROA further enhance the quality of sustainability reporting. DER negatively affects the quality of sustainability reporting. Whereas BD_ID, AU_CM, CR and SIZE are proven to have no effect on the quality of sustainability reporting.